2013
DOI: 10.1128/aac.00063-13
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of Microbe Sterilization by Cationic Antimicrobial Peptides

Abstract: We recently described a family of cationic antimicrobial peptides (CAMPs) selected from a combinatorial library that exhibited potent, broad-spectrum activity at neutral pH and low ionic strength. To further delimit the utility and activity profiles of these peptides, we investigated the effects of solution conditions, such as pH and ionic strength, on the efficacy of the peptide antimicrobials against a panel of microorganisms. Peptide minimum sterilizing concentrations (MSCs) varied linearly with pH for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 55 publications
1
48
0
Order By: Relevance
“…These observations clearly suggest that when characterizing the antimicrobial action of AMPs, the optimal pH for their action against individual microbes should be determined. This point is well illustrated by recent studies, which investigated the antimicrobial action of a range of synthetic AMPs and found that high pH inhibited the action of these peptides against fungi and Gram-negative bacteria but the opposite pH trend was observed for Gram-positive bacteria [302]. …”
Section: Discussionmentioning
confidence: 75%
“…These observations clearly suggest that when characterizing the antimicrobial action of AMPs, the optimal pH for their action against individual microbes should be determined. This point is well illustrated by recent studies, which investigated the antimicrobial action of a range of synthetic AMPs and found that high pH inhibited the action of these peptides against fungi and Gram-negative bacteria but the opposite pH trend was observed for Gram-positive bacteria [302]. …”
Section: Discussionmentioning
confidence: 75%
“…In the case of His-containing peptides, the enhancement occurs due to an increase in peptide net charge and a facilitated translocation (Kacprzyk et al, 2007). This hypothesis is well illustrated in recent studies showing that high pH inhibited the antifungal activity of synthetic peptides (Walkenhorst, Klein, Vo, & Wimley, 2013), although some peptides display better activity at higher pH (Hajji et al, 2010). In order to provide a larger pH range, dimers (P-113) can be created, although a deeper understanding of the effect on peptide antifungal activity is needed.…”
Section: Effect Of Temperature Ph and Proteolysismentioning
confidence: 71%
“…In contrast, salt and serum had clear effects on the activity of other AMPs such as human beta defensin 3 (hBD-3). 42, 43 …”
Section: Resultsmentioning
confidence: 99%